Insumos para la renovación de los Registros Calificados de los programas de Maestría en Pedagogía, Maestría en Dirección y Gestión de Instituciones Educativas y Maestría en Desarrollo Infantil de la Universidad de La Sabana Extensión Riohacha La Guajira (2025)
La Sabana University has three Master Programs in The Guajira-Colombia Extension, whose Qualified Registers are about to finish, depending on at least two factors: The Registers expiration dates and the Institutional High Quality Accreditation expiration date. In the first case, it is necessary to request the renovation by previous accomplishing of twelve Analysis Factors. In the second case, it is mandatory to update the High Quality Accreditation, to facilitate the subsequent Register Renovation. On the other side, the Institution has the challenge to begin the transition to Third Generation University (3GU), according to the proposal of Obdulio Velásquez, the Principal on 2020. This research pretends to give some orientations and reflections around the requirements of both targets, the Registers Renovation process and the re-direction of the Institutional Mission so that the transition to 3GU be possible.